All passive participles are adjectival - García-Pardo, Alfredo (Borealis – An International Journal of Hispanic Linguistics, 2024)
This paper argues that the passive participles in eventive passives (what is commonly referred to as 'verbal passives') are adjectival in Spanish. Thus, there is no categorial difference between eventive and stative passives (the latter commonly known as `adjectival passives'. I show that the differences between eventive and stative passive participles, and the argument structure configurations that each type allows, can be accounted for without the need to posit a different morphological category for each type. Rather, the grammatical context in which the participle is inserted will allow for a simpler (stative) or more complex (eventive) structure for the base verb. I thus also argue against a stativization operation in stative passives: what we have is a base verb that only spells out the result state of the event, not a verb that spells out a telic structure and then is stativized by a purported higher operator.